2011
DOI: 10.1007/s00213-011-2478-y
|View full text |Cite
|
Sign up to set email alerts
|

Restricted role of CRF1 receptor for the activity of brainstem catecholaminergic neurons in the negative state of morphine withdrawal

Abstract: Our study demonstrates an increased activity of brainstem catecholaminergic neurons after CPA induced by morphine withdrawal suggesting that CRF1R is implicated in the activation of A1 neurons and provides evidence that this receptor is involved in the body weight loss and in the negative aversive effects of morphine withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…Our results are consistent with findings from our laboratory demonstrating that CRF1 receptor is not implicated in the enhancement of NA turnover in the PVN, which receives projections from NTS, observed during morphine withdrawal [33]. In addition, a previous study using CRF1receptor-deficient mice demonstrated that CRF1 receptor is not responsible for the phosphorylation of TH observed in NTS after naloxone-precipitated withdrawal in wild-type mice [56].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with findings from our laboratory demonstrating that CRF1 receptor is not implicated in the enhancement of NA turnover in the PVN, which receives projections from NTS, observed during morphine withdrawal [33]. In addition, a previous study using CRF1receptor-deficient mice demonstrated that CRF1 receptor is not responsible for the phosphorylation of TH observed in NTS after naloxone-precipitated withdrawal in wild-type mice [56].…”
Section: Discussionsupporting
confidence: 93%
“…Together, all these data implicated NA neurons in NTS in the aversiveness of acute opioid withdrawal. Support for this idea can be found in a number of studies that implicate the NTS-A2 noradrenergic cells group in that affective disorder associated with drug withdrawal [6], [54][56]. Changes in the state of phosphorylation of TH, the rate limiting enzyme in the synthesis of catecholamines, are critically involved in the regulation of catecholamines, synthesis and function.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies have reported that immobility and climbing behavior in the FST are associated with the central noradrenergic system [21]. Also, many studies have suggested that morphine dependence and withdrawal show increases the number of TH positive neurons in the LC [22,23]. Activation of the LC produces intense anxiety, hypervigilance and inhibition of exploratory behavior [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…A CRF 1 antagonist also prevented the development of a conditioned place aversion following precipitated withdrawal in opioid-dependent rats (Stinus, Cador, Zorrilla, & Koob, 2005). Similarly, Crhr1 knockout mice did not show opioid withdrawal-induced conditioned place aversion (Contarino & Papaleo, 2005; Garcia-Carmona, Almela, Baroja-Mazo, Milanes, & Laorden, 2012). Finally, systemic injections of brain-penetrant CRF 1 antagonists reduced the heightened anxiety-like behavior of dependent rodents acutely withdrawn from alcohol or other substances of abuse (Breese, Overstreet, & Knapp, 2005; Breese, Overstreet, Knapp, & Navarro, 2005; Gehlert et al, 2007; Knapp et al, 2004; Overstreet et al, 2004; Sommer et al, 2008).…”
Section: Role For Crf-crf1 Systems In Animal Models Of Addictionmentioning
confidence: 97%